Description of the male of Pterorthochaetes yunnanensis Ballerio, 2014 (Coleoptera: Scarabaeoidea: Hybosoridae: Ceratocanthinae) - Jiang, Ri-Xin; Ballerio, Alberto; Liu, Hao-Yi; Wang, Shuo (Zootaxa, 2021)
The ceratocanthine genus Pterorthochaetes Gestro, 1898 (Coleoptera: Scarabaeoidea: Hybosoridae) includes about 26 valid species and occurs from the eastern Himalaya (Nepal and India) and southern China to northern Australia (Queensland) and Vanuatu Islands (Paulian 1978, 1987; Ballerio 1999, 2006, 2013, 2014).